Fragmentos (literarios, pedagógicos, filosóficos) de una crítica de la razón evaluadora. (2020)
In these pages a composition consisting of literary, philosophical and pedagogical fragments is invited, which converses (in)directly with each other. In turn, the pieces presented here are part and art of a broader philosophical-literary investigation that essay a "critique of evaluative reason" and explores its ethical-political implications in education. In this context, the proposed journey contains different critical movements that begin in their first two moments with one foot in childhood (understood in a non-chronological way) and with another foot in philosophical discussion. Subsequently, the anecdotal and the philosophical are interwoven in a reflection on a criticism of the fetishism of the notes and a celebration of the transgressive (and artistic) action of copying. In this way, we continue pointing out some problems with the word ‘request’, which is also related to extractivism about intelligence and sometimes ends up making the subject want the evaluation. In addition, go to the cinema for rethinking some consequences of formation that privileges the evaluative over the educational and an antecedent that contributes to its decolonization is contrasted. Finally, the exit takes the form of excursion through insubordination, the pedagogical strike and laziness as forms of resistance and re-existence.